Romantisasi atau Pembebasan? Kritik Feminisme Terhadap Representasi Perempuan dalam ’Hanya Dalam Puisi’ Karta Ajip Rosidi - Ridwan, Ridwan; Inhilda, Inul (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This study examines the dynamics of women’s presence in Indonesian poetry after the New Order through a feminist approach. The main focus of this study is how women are depicted in literary works, and how poetry functions as a medium to convey the experiences and problems faced by women in a patriarchal society. Using qualitative descriptive methods, this study analyzes various poems that represent the image and voice of women, and highlights issues of gender equality and oppression experienced by women. The results of the study show that poetry is not only a means of expression, but also a tool to fight for women’s rights and challenge existing gender stereotypes. This study is expected to contribute to a deeper understanding of the role and position of women in literature and society. Overall, these poems not only voice women’s experiences, but also provoke thought about gender equality and oppression, and offer a space for struggle and liberation through creative expression. Using a feminist approach, this study reveals that poetry can function as a critical tool that fights for women’s rights and challenges inequality in patriarchal society.